Impact of Drinking Water Treatment Process Using Life Cycle Assessment (LCA) to Minimize Environmental Impact Risk - Ika Bayu Kartikasari; R. Irwan Bagyo Santoso (Journal of Social Research, 2023)
The clean water treatment plant at DWTP is carried out with conventional treatment. The conventional water treatment process has an impact on the environment due to the clean water treatment process. Clean water treatment produces GWP and Eutrophication impacts derived from the use of chemicals and electricity. This study aims to analyze the factors causing environmental impacts arising from the clean water treatment process at the PDAM Water Treatment Plant (IPA) and determine policy priorities related to reducing environmental impacts and improving the quality of drinking water treatment at the Water Treatment Plant based on the results of LCA and AHP studies. The Life Cycle Assessment (LCA) method is a method of assessing the potential environmental impact and evaluating the environmental performance of a process on the product. Life Cycle Assessment (LCA) consists of four stages, namely determination of Goal and Scope, Life Cycle Inventory, Life Cycle Impact Assessment, and data interpretation. In research, the scope of LCA used is Gate to Gate, namely in the Coagulation, Flocculation, and Sedimentation process units. From the results of the LCA study, the potential impact of GWP of 12760.76 KgCO2-eq comes from flocculation which produces floc from the addition of chemicals. Meanwhile, the potential impact of eutrophication is 268.55 KgPO4-eq derived from mud generation. The results of the decision in reducing environmental impact at DWTP by optimizing chemicals as a top priority, then the second priority by recycling sludge, and finally making savings and energy alternatives are the last priority. Each respondent's score reached 55%, 23% and 22%. The results of the implementation of the program if implemented can reduce the impact of GWP 20079.17 kg CO2-eq and the impact of eutrophication can be reduced by 201.401 kg PO4-eq.mportant matters discussed in the paper that significantly contribute to the final result of the research may be noted here, but you have to consider, however, the limited space of the abstract.